Financial Well-Being Pelaku UMKM di Wilayah Kepulauan: Peran Mediasi Financial Behavior - Simon Hendrik Leasa; Hanifa Bennu Nur; Semuel Souhoka; Nur Azda (ARBITRASE: Journal of Economics and Accounting, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in archipelagic regions face economic challenges, including limited economic access, high logistics costs and business instability, which may adversely affect financial well-being. Although research on financial well-being has grown substantially, studies examining the mediating role of financial behavior among MSMEs in archipelagic regions remain limited. Therefore, this study examines the effects of financial literacy and financial self-efficacy on financial well-being through financial behavior among MSME owners in Ambon City, Maluku Province. A quantitative explanatory research design was employed involving 120 MSME owners selected through purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results indicate that financial literacy positively affects financial behavior (? = 0.216, p = 0.009), while financial self-efficacy also has a positive effect (? = 0.498, p < 0.001). Financial behavior positively affects financial well-being (? = 0.527, p < 0.001) and significantly mediates the relationships between financial literacy, financial self-efficacy, and financial well-being. Financial self-efficacy also exerts a stronger influence than financial literacy in shaping financial behavior. The novelty of this study lies in developing a behavioral mechanism-based financial well-being model for MSMEs in archipelagic regions. The findings contribute to the behavioral finance literature by providing empirical evidence on the behavioral mechanisms underlying financial well-being and offer practical implications for designing programs that strengthen financial literacy, financial self-efficacy and adaptive financial behavior to enhance MSMEs' financial resilience.